2021
DOI: 10.1016/j.jallcom.2021.159728
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite (Sr2Ta2O7)100−x(La2Ti2O7)x ceramics: From dielectric characterization to dielectric resonator antenna applications

Abstract: In this paper, ferroelectric ceramics with (Sr 2 Ta 2 O 7 ) 100-x (La 2 Ti 2 O 7 ) x (STLTO) compositions have been investigated and their dielectric properties have been characterized in wide frequency band (from few kHz to few GHz); their integration in Dielectric Resonator Antennas (DRA) was conducted. The dense STLTO ceramics have been obtained by high temperature sintering of powders synthetized by solid state chemistry route. STLTO crystalline cell parameters and volume vary linearly as a function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These modes displacement to the right as the O 2 concentration increases, whereas this change observed in the frequency could be explained by the variation of resistance of GO film when there is an interaction of the O 2 with graphene on the GO surface, taking the alteration of the device impedance and resulting the displacement of its frequency of operation [36,37]. In addition, it was observed that the reflection coefficient (S 11 ) also increased with the O 2 concentration but remained below −10 dB, which is a requirement for a device operating as an antenna [38,39]. This result is important because it demonstrates that the device evaluated act as an antenna at the O 2 elevated concentrations.…”
Section: Numerical Simulationmentioning
confidence: 98%
“…These modes displacement to the right as the O 2 concentration increases, whereas this change observed in the frequency could be explained by the variation of resistance of GO film when there is an interaction of the O 2 with graphene on the GO surface, taking the alteration of the device impedance and resulting the displacement of its frequency of operation [36,37]. In addition, it was observed that the reflection coefficient (S 11 ) also increased with the O 2 concentration but remained below −10 dB, which is a requirement for a device operating as an antenna [38,39]. This result is important because it demonstrates that the device evaluated act as an antenna at the O 2 elevated concentrations.…”
Section: Numerical Simulationmentioning
confidence: 98%
“…We have demonstrated the ferroelectric behavior of the p-STLTO family of compounds in the form of ceramics for (Sr2Ta2O7)100-x(La2Ti2O7)x compositions with x ranging from 0 to 5 [7]. Optimal characteristics were achieved for x = 1.65: the permittivity value was ' = 375 with a high tunability T = 55 % at 30 kV/cm, 10 kHz and room temperature [8], associated to low dielectric losses tan = 2.10 -3 . Our work then focused on the transfer of the specific composition corresponding to x = 1.65 in the thin films form.…”
Section: Introductionmentioning
confidence: 96%
“…These materials are renowned for their broad spectrum of multifunctional properties, including ferroelectricity, piezoelectricity, pyroelectricity, ferromagnetism, and nonlinear dielectric characteristics [2][3][4][5][6]. Such diverse properties make them suitable for a variety of applications, encompassing energy conversion and storage, sensors, filters, separators, detectors, antennas, and environmental remediation [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%